Altering the Reflection Phase for Nano‐Polaritons: A Case Study of Hyperbolic Surface Polaritons in Hexagonal Boron Nitride. Issue 13 (30th April 2022) - Chen, Mingyuan; Sanders, Stephen; Shen, Jialiang; Li, Jiahan; Harris, Eli; Chen, Cheng‐Chien; Ma, Qiong; H. Edgar, James; Manjavacas, Alejandro; Dai, Siyuan
Abstract: Polaritons—confined light–matter waves—in van der Waals (vdW) materials are a research frontier in light–matter interactions with demonstrated advances in nanophotonics. Reflection, as a fundamental phenomenon involving waves, is particularly important for vdW polaritons, predominantly because it enables the investigation of polariton standing waves using the scanning probe technique. While previous works demonstrate a rigid phase ≈π/4 for the polariton reflection, herein is reported the altering of the polariton reflection phase by varying the geometry of polaritonic microstructures for the case study of hyperbolic surface polaritons (HSPs) in hexagonal boron nitride (hBN). Specifically, it is demonstrated that the polariton reflection phase can be systematically altered by varying the corner angle of the hBN microstructures, and that it experiences a π jump around a specific angle. This behavior, which is a consequence of the mathematical nature of the reflection coefficient, is therefore expected in other physical phenomena. Abstract : Through a combined experimental and theoretical investigation, it is demonstrated that the reflection phase of hyperbolic surface polaritons propagating in hexagonal boron nitride (hBN) microstructures can be systematically altered by varying the corner angle of the hBN structure, and that it experiences a π jump around a specific angle.